CYP21A2 Genotypes do not Predict the Severity of Hyperandrogenic Manifestations in the Nonclassical Form of Congenital Adrenal Hyperplasia - Moura-Massari, V. O.; Bugano, D.D. G.; Marcondes, J.A. M.; Gomes, L. G.; Mendonca, B. B.; Bachega, T.A.S. S. (Hormone and Metabolic Research, 2013)
There is a strong correlation between the severity of genotypes and 17OH-progesterone levels in patients with the nonclassical form of 21-hydroxylase deficiency (NC-CAH); however, there are few studies regarding the correlation with clinical signs. The aim of the study was to evaluate whether genotypes correlate with the severity of the hyperandrogenic phenotype. A cohort of 114 NC-CAH patients were diagnosed by stimulated-17OHP ≥10 ng/ml. CYP21A2 genotypes were divided into 2 groups according to the severity of enzymatic impairment; mild and severe. Clinical data and hormonal profiles were compared between the 2 groups. Age at onset of manifestations did not differ between children or adults carrying both mild and severe genotypes. Frequencies of precocious pubarche and hirsutism, with or without menstrual abnormalities, were similar between the 2 groups. There were no differences in basal testosterone levels of adult symptomatic females carrying both genotypes, but there were differences between adult females with (92.9±49.5 ng/dl) and without hirsutism (43.8±38 ng/dl) (p=0.0002). Similar frequencies of both genotypes were observed in asymptomatic females and in those with clitoromegaly. Nonclassical genotypes do not predict the severity of phenotype. Asymptomatic and virilized females carrying the same genotype suggest that there is a modulatory effect of genes involved in the androgen pathway on the phenotype.
Keywords: 21-hydroxylase deficiency; genotype/phenotype correlation; hyperandrogenic manifestations; allelic distribution; nonclassical form